Traditional Media, Twitter, and Four Business Scandals - John Jiang; Michael Shen (Journal of Quantitative Description: Digital Media)
We examine how traditional media and Twitter cover four business scandals: Wells Fargo fake accounts, EpiPen pricing hikes, Samsung Note 7 faulty battery, and Volkswagen’s cheating in emission tests. There are over 500 articles from The Wall Street Journal, The New York Times, The Washington Post, and USA Today, and over 400,000 tweets related to these events. We find that traditional media are highly influential. Media organizations, including newspapers, TV networks, and other media outlets, only sent 1% of the scandal-related tweets, but they account for 39% of Twitter users who follow all scandal-related tweets. Newspaper articles rather than individual tweets drew politicians’ attention and preceded additional responses from the troubled firms. The troubled firms also choose TV instead of social media to speak to the public. In contrast, social media appear to play a discovery role. Individual tweets precede newspaper articles but not vice versa. Overall, we conclude that the rise of social media such as Twitter does not diminish the role of traditional media in covering business scandals.